Comparison of the chemistry and diversity of endophytes isolated from wild-harvested and greenhouse-cultivated yerba mansa (Anemopsis californica). (March 2015) - Bussey, Robert O.; Kaur, Amninder; Todd, Daniel A.; Egan, Joseph M.; El-Elimat, Tamam; Graf, Tyler N.; Raja, Huzefa A.; Oberlies, Nicholas H.; Cech, Nadja B.
Graphical abstract: Highlights: Fourteen fungal endophytes were isolated from yerba mansa ( Anemopsis californica ). Chaetomium cupreum yielded a new antimicrobial spirolactone, chaetocuprum. Endophyte diversity was higher from wild-harvested than cultivated roots. Results indicate the importance of source material for endophyte drug discovery. Abstract: With this study, we explored the identity and chemistry of fungal endophytes from the roots of yerba mansa [ Anemopsis californica (Nutt.) Hook. & Arn. (Saururaceae)], a botanical traditionally used to treat infection. We compared the diversity of fungal endophytes isolated from a wild-harvested A. californica population, and those from plants cultivated for one year in a greenhouse environment. The wild-harvested population yielded thirteen fungal strains (eleven unique genotypes). Of the extracts prepared from these fungi, four inhibited growth of Staphylococcus aureus by >25% at 20 μg/mL, and three inhibited growth of Pseudomonas aeruginosa by ≥20% at 200 μg/mL. By comparison, A. californica roots after one year of cultivation in the greenhouse produced only two unique genotypes, neither of which displayed significant antimicrobial activity. The fungus Chaetomium cupreum isolated from wild-harvested A. californica yielded a new antimicrobial spirolactone, chaetocuprum (1 ). An additional 14 known compounds were identified using LC–MS dereplication of the various fungal endophytes. This study provides new insights into the identity and chemistry of A. californica fungal endophytes, and demonstrates the importance of considering growing conditions when pursuing natural product drug discovery from endophytic fungi.